VALUES CLARIFICATION TECHNIQUE AND SELF-CONCEPT IN INSTILLING ELEMENTARY STUDENTS’ SOCIAL ATTITUDES - Badruli Martati; Makruf Akbar; M Syarif Sumantri (Universitas Negeri Medan, 2019)
Abstract : This study was aimed to investigate the effect of values clarification technique (VCT) and self-concept in instilling the social attitudes of elementary school students. This study used an experimental research design. The subjects were 44 students from Sedati Gede Public Elementary School in Sidoarjo. The experimental design used the level 2 x 2. The results showed that the use of VCT on elementary school students better than conventional approach learning in developing their social attitudes. This indicated that VCT had a significant impact on social attitudes of the students and the impact depended on the state of self-concept of the students. The awareness toward the positive values that sholud be done and negative that should be avoided such as saying thanks, showing discipline, obeying the rules, keeping the promises, and having the sense of curiosity, showing tolerance, honesty and responsibility. In addition, this study extended our knowledge that expository made teacher play a role in transferring knowledge to students. Ergo students passively accepted the moral values. Keywords: elementary school, values clarification technique, social attitudes, self-concept Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh teknik klarifikasi nilai (VCT) dan konsep diri dalam menanamkan sikap sosial siswa sekolah dasar. Penelitian ini menggunakan desain penelitian eksperimental. Subjek penelitian adalah 44 siswa dari SDN Sedati Gede di Sidoarjo. Desain eksperimental menggunakan level 2 x 2. Hasil penelitian menunjukkan bahwa penggunaan VCT pada siswa sekolah dasar lebih baik daripada pendekatan pembelajaran konvensional dalam mengembangkan sikap sosial mereka. Ini menunjukkan bahwa VCT memiliki dampak yang signifikan terhadap sikap sosial siswa dan dampaknya tergantung pada konsep diri siswa. Kesadaran terhadap nilai-nilai positif yang harus dilakukan sholud dan negatif yang harus dihindari seperti mengucapkan terima kasih, menunjukkan disiplin, mematuhi aturan, menepati janji, dan memiliki rasa ingin tahu, menunjukkan toleransi, kejujuran dan tanggung jawab. Selain itu, penelitian ini memperluas pengetahuan kami bahwa ekspositori membuat guru berperan dalam mentransfer pengetahuan kepada siswa. Siswa Ergo secara pasif menerima nilai-nilai moral. Keywords: sekolah dasar, teknik klarifikasi nilai, sikap sosial, konsep diri